A healthy pregnancy following chemotherapy for dysgerminoma - Begum, H; Nahar, K; Moniruddin, ABM; Majumder, NA (Journal of Armed Forces Medical College, Bangladesh, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> doi:10.3329/jafmc.v4i2.1846 JAFMC Bangladesh Vol.4(2) 2008 42-43